ICG Lymphography Confirms the Presence of an Alternative Lymph Drainage Pathway Following Long-Term Manual Therapy: A Case for Preserving Traditional MLD Approaches - Mary Wakefield; Jan Douglass; Diane Lacey; Neil Piller; Linda Blanchfield (Reports)
Background and Clinical Significance: Breast cancer-related lymphedema (BCRL) is a chronic condition affecting up to 20% of breast cancer survivors. Manual lymphatic drainage (MLD) has traditionally included techniques to redirect lymph flow toward alternative pathways when axillary drainage is impaired. However, emerging imaging techniques suggest that most lymph continues to drain toward the ipsilateral axilla, and this has led to the widespread uptake of treatment protocols that exclude traditional redirecting movements, even in cases where personalized imaging is unavailable. Case Presentation: This case report describes a woman with BCRL affecting the right arm and hand who underwent 3 years of conservative lymphedema therapy, including MLD and self-massage techniques that incorporated traditional redirection strategies. Pre-operative indocyanine green (ICG) lymphography, performed after prolonged conservative treatment, confirmed the presence of an open alternative drainage pathway bypassing the axilla and demonstrated dermal flow along the redirected pathways towards a previously described “radial” pathway. These findings suggest that targeted manual therapy may have reinforced or optimized this compensatory route. Conclusions: This case highlights the potential risk of relying on a single form of assessment and generalized cohort imaging studies to guide individualized MLD protocols. In the absence of personal imaging, prematurely abandoning traditional redirection techniques may limit opportunities to establish functional alternative pathways, particularly in early edema in patients who have this anatomical variation. ICG lymphography provides valuable insight into compensatory lymphatic drainage. However, until imaging protocols are standardized and individual imaging is widely accessible, retaining traditional MLD techniques for newly diagnosed BCRL may be crucial for optimizing treatment outcomes. Future research should explore the long-term impact of manual therapy on alternative pathway development and function.